2019
DOI: 10.1108/pr-05-2018-0158
|View full text |Cite
|
Sign up to set email alerts
|

Talent management in a Swedish public hospital

Abstract: PurposeThe purpose of this paper is to contribute to the understanding of how talent management (TM) unfolds in practice in a public organization.Design/methodology/approachAn exploratory single case study was conducted of a Swedish public hospital, based on interviews, observations and documents.FindingsThe findings illustrate that despite a highly egalitarian and collectivist context, the hospital adopted an exclusive approach to TM, and a talent was not considered or identified through formal performance ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 65 publications
0
42
0
Order By: Relevance
“…The results were consistent with the hypothesis and literature. Hence, the study hypothesis was accepted because studies have shown that talent management has a great impact on individual level biographical factors such as promotion opportunities, years of work experience, education qualification, age and hours' work in a particular work (Barkhuizen et al, 2014a, b, c;Tyskbo, 2019) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were consistent with the hypothesis and literature. Hence, the study hypothesis was accepted because studies have shown that talent management has a great impact on individual level biographical factors such as promotion opportunities, years of work experience, education qualification, age and hours' work in a particular work (Barkhuizen et al, 2014a, b, c;Tyskbo, 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…Talent deployment: This entails placing employees to various sections to make sure that no department/section is overstaffed or understaffed (Tyskbo, 2019).…”
Section: Talent Management Practicesmentioning
confidence: 99%
“…6) Talent deployment: This entails placing employees into various sections to make sure that no department/section is overstaffed or understaffed (Tyskbo 2019). 7) Talent engagement: This is the process of allowing employees to be involved fully in the activities of the organisation.…”
Section: Talent Management Practicesmentioning
confidence: 99%
“…There are numerous benefits of talent management. Most importantly, talent management helps an organisation to retain the potential talented workforce to stay in the existing organisation (Olusegun, Akinwale, and James 2020;Tyskbo 2019).…”
Section: Talent Management Practicesmentioning
confidence: 99%
“…Most of the research focuses on the private sector organisation context, and very few studies concentrate on public sector organisations. The problem of insufficient research has been mentioned by Poocharoen and Lee (2013), Thunnissen and Buttiens (2017) and Tyskbo (2019). Some scholars have highlighted that appropriate talent identification is vital in developing an effective TM system (Mellahi and Collings, 2010; McDonnell et al , 2011; Ross, 2013; Lai and Ishizaka, 2020).…”
Section: Introductionmentioning
confidence: 99%